Risque palustre : appréhender la vulnérabilité des individus à l'échelle locale (Sud du Bénin) - Charlotte Pierrat (VertigO)
Malaria still is today one of the most fatal pandemic disease of southern countries. The majority of populations at risk live in sub-Saharan Africa. It’s indeed a vector-borne disease deeply linked with a hot and wet climate. But the prediction models of malaria, mainly based on climate, fail to explain the spatial and temporal variability of transmission observed on the very fine scale of a rural village. Shortcomings of the main models based on climatic and entomological knowledge on a micro-scale are due to the difficulty of collecting sharp climatic data and other socio-economic variables that determine the vulnerability of populations – poorly taken into account so far in the prediction of malaria risk. Fieldwork in Tori Bossito, a rural district in southern Benin, has allowed analyzing the socio-eco-environmental factors of malaria on a local scale. Results confirm the great spatial heterogeneity of transmission on a very fine scale, and show that it is linked to factors of vulnerability identified at the household scale.